ARTISTIC INTERPRETATION OF THE IMAGE OF THE WRITER – JADIDA - Mansurova Malika Askarovna (Journals Park Publishing, 2024)
This article analyzes the story “Flower of Hope” by the famous Uzbek writer Khurshid Dostmuhammad, the author focuses on the specificity of creating the image of Fitrat, as well as the author's skill in creating the image of the writer. The article also examines the role of historical sources in creating the image of the main character, and the interpretations that the writer was guided by.
Keywords: story, image of a creative person, artistic interpretation, poetic skill, historical truth.